Game-Based Learning as a Pedagogical Innovation Model in Islamic Education - Abdul Hamid; Mahmutarom Mahmutarom; Sari Hernawati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study investigates the implementation of Game-Based Learning (GBL) as an innovative pedagogical model in contemporary Islamic Education at MTs Negeri 1 Kota Semarang. The research was motivated by the continued use of conventional teaching methods, which often resulted in low student engagement, limited interaction, and reduced learning motivation among Grade VIII students. Employing a qualitative case study approach, data were collected through classroom observations, semi-structured interviews, and documentation analysis involving Islamic Religious Education teachers and students. The findings indicate that the use of digital platforms such as Quizizz, Kahoot, and Wordwall transformed the learning process into a more interactive, collaborative, and student-centered experience. Students showed higher participation, stronger motivation, improved teamwork, and better understanding of fiqh and Islamic Cultural History materials. Moreover, teachers adapted their roles from traditional knowledge transmitters to learning facilitators. The study also found that GBL effectively integrated Islamic values, including honesty, responsibility, cooperation, and discipline, making it a promising approach for enhancing learning effectiveness in modern madrasah education.